Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Direct hydrothermal synthesis of highly ordered Sn-SBA-15 mesoporous materials - Shah, Pallavi; Ramaswamy, Arumugamangalam V.; Ramaswamy, Veda (Chemistry Letters, 2006)
Well-ordered Sn4+-incorporated mesoporous silica SBA-15 samples have been synthesized from tetraethyl orthosilicate (TEOS) and SnCl4 (Si/Sn = 114-15) using nonionic surfactants under a slightly higher pH medium (optimum H2O to HCl molar ratio) and characterized by XRD (an increase in lattice parameter), TEM (no SnO2 species) and UV-vis spectral (absorption at 211 nm) techniques to show that Sn4+ ions are in tetrahedral coordination in Sn-SBA-15.

Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania

Oxidation of aniline over titania pillared montmorillonite clays - Jagtap, Neelam; Ramaswamy, Veda (Applied Clay Science, 2006)
Titania pillared clays (Ti-PILC) have been synthesized employing conventional stirring (method I) and ultrasonic agitation (method II) techniques followed by hydrothermal treatment. The characterization results revealed the formation of Ti-PILC with significant reduction of time when ultrasonic method was used. Subsequent hydrothermal treatment on the samples has resulted in the increase in the crystallinity and the transformation of anatase TiO2 to rutile TiO2. The rutile phase is more prominent in the samples prepared by stirring method. UV-Vis studies on the samples exhibit blue shift in the absorption band due to the quantum size effect. This indicates that a major part of TiO2 in the pillared clay could be well below 10 nm in size, which is supported by XRD and the average pore size. The pillared clay catalysts have proved to be promising in aniline oxidation with H2O2, selectively forming azoxybenzene under the working conditions. The aniline conversion and the product distribution largely depended on the catalyst concentration, H2O2 to aniline mole ratio, the nature of the solvent and the oxidant. Higher conversion of aniline and greater selectivity for azoxybenzene was obtained with methanol as the solvent. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: aniline oxidation; Azoxybenzene; hydrothermal treatment; pillared clays

Direct hydrothermal synthesis of mesoporous Sn-SBA-15 materials under weak acidic conditions - Shah, P.; Ramaswamy, A. V.; Lazar, Karoly; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2007)
A direct synthetic route for the preparation of Sn-SBA-15 materials with n(Si)/n(Sn), ratios ranging from 100 to 10 under milder acidic conditions than normally employed for the preparation of Si-SBA-15 is reported. The changes in the pH conditions of the gel were made through an adjustment of the molar ratio of n(H2O) to n(HCl) (< 1 pH < 2) during preparation. The samples prepared under three different acidic conditions have been characterized by various techniques. An expansion of the lattice (powder XRD) and an increase in mesopore area (low temperature N-2 adsorption) indicate that the hexagonal structure of the SBA- 15 is maintained with no loss of long range ordering. The UV-vis reflectance spectra of Sn-SBA-15 samples show the presence of Sn4+ ions both in tetrahedral and octahedral environment. Si-29 MAS NMR spectra of samples prepared under an intermediate acid condition show the presence Of Q(3) and Q(4) species. Their ratio increases with a decrease in tin content. The presence of Si in (2Si, 2Sn) i.e., Q(2) environment may point to incorporation of considerable Sn4+ ions in tetrahedral positions. Sn-Mossbauer spectroscopic studies reveal that Sn2+ species form upon reductive treatments and can probably be stabilized in the pore wall upon reoxidation. This to some extent is an indication of the formation and stabilization of Si-O-Sn-O-Si linkages in Sn-SBA-15. A progressive increase in the pH of the medium (increasing the n(H2O) to n(HCl), ratio) results in the location of Sn4+ ions, (a) at the surface of the mesopores (surface of the corona region) as a thin film of SnO2 or small aggregates (loss in mesopore area) depending on the concentration of Sn; (b) at the walls of the mesopore structure, substituting Si4+ ions (some lattice expansion and tetrahedral Sn4+ ions); and/or (c) as a part of the corona region, neutralizing the resulting Si-OH groups (a loss of micropore area and octahedral Sn4+ ions). The studies reveal that the method of preparation, n(H2O)/n(HCl) ratio and the n(Si)/n(Sn) ratio (concentration of SnCl4) of the gel significantly influence the type of tin species in the resulting Sn-SBA-15 samples. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: direct synthesis of Sn-SBA-15; Si-29 and Sn-119 MAS-NMR; Sn-mossbauer spectroscopic studies; Sn-SBA-15; tin-mesoporous silica

Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.

NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Thermal stability of the Mobil Five type metallosilicate molecular sieves - an in situ high, temperature X-ray diffraction study - Bhange, Deu S.; Ramaswamy, Veda (Materials Research Bulletin, 2007)
We have carried out in situ high temperature X-ray diffraction (HTXRD) studies of silicalite-1 (S-1) and metallosilicate molecular sieves containing iron, titanium and zirconium having Mobil Five (MFI) structure (iron silicalite-1 (FeS-1), titanium silicalite-1 (TS-1) and zirconium silicalite-1 (ZrS-1), respectively) in order to study the thermal stability of these materials. Isomorphous substitution of Si4+ by metal atoms is confirmed by the expansion of unit cell volume by X-ray diffraction (XRD) and the presence of Si-O-M stretching band at similar to 960 cm(-1) by Fourier transform infrared (FTIR) spectroscopy. Appearance of cristobalite phase is seen at 1023 and 1173 K in S-1 and FeS-1 samples. While the samples S-1 and FeS-1 decompose completely to cristobalite at 1173 and 1323 K, respectively, the other two samples are thermally stable upto 1623 K. This transformation is irreversible. Although all materials show a negative lattice thermal expansion, their lattice thermal expansion coefficients vary. The thermal expansion behavior in all samples is anisotropic with relative strength of contraction along `a' axes is more than along `b' and V axes in S- 1, TS-1, ZrS-1 and vice versa in FeS-1. Lattice thermal expansion coefficients (alpha(v)) in the temperature range 298-1023 K were -6.75 x 10(-6) K-1 for S-1, -12.91 x 10(-6) K-1 for FeS-1, -16.02 x 10(-6) K-1 for TS-1 and -17.92 x 10(-6) K-1 for ZrS-1. The highest lattice thermal expansion coefficients (alpha(v)) obtained were -11.53 x 10(-6) K-1 for FeS-1 in temperature range 298-1173 K, -20.86 x 10(-6) K-1 for TS-1 and -25.54 x 10(-6) K-1 for ZrS-1, respectively, in the temperature range 298-1623 K. Tetravalent cation substitution for Si4+ in the lattice leads to a high thermal stability as compared to substitution by trivalent cations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; Thermal expansion; X-ray diffraction

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Cu-Ce mixed oxides supported on Al-pillared clay: effect of method of preparation on catalytic activity in the preferential oxidation of carbon monoxide - Ramaswamy, Veda; Malwadkar, Sachin S.; Chilukuri, Satyanarayana V. (Applied Catalysis B-Environmental, 2008)
The possibility of using Al-pillared montmorillonite (Al-PILC) clay as a high-surface-area support for CuO-CeO2-based catalysts has been investigated. The preparation of the samples was done by three different methods, viz., amorphous citrate route (ACR), deposition precipitation (DP) and wet impregnation method (WIM). Samples with different CuO-CeO2 loadings (10-50 wt.%) were prepared by each of the three methods. The catalytic activity of these samples was investigated for the preferential oxidation (PROX) of carbon monoxide (CO) in excess of H-2. The samples prepared by DP and WIM methods show better activity than the samples prepared by ACR method. At low Cu content, the samples prepared by DP method have a slight edge over samples prepared by WIM method. The DP-30 sample shows a very high CO conversion of 96.1% at 423 K. A higher dispersion of CuO-CeO2 on pillared montmorillonite clay and better reducibility of copper oxide species may be responsible for the good activity of these samples even at lower reaction temperatures. A higher O-2/CO ratio increased the CO conversion but led to a reduction in oxidation selectivity. No methanation of CO or CO2 was observed at the reaction temperature. These CuO-CeO2/Al-PILC samples could be considered as comparable in performance with supported noble metal catalysts for the preferential oxidation of CO in excess hydrogen. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alumina-pillared clay; Clay-supported CuO-CeO2; CuO-CeO2; PROX of CO

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Non-isothermal kinetic studies of the template decomposition from silicalite-1 framework-high temperature X-ray diffraction and thermogravimetric analysis - Bhange, Deu S.; Pandya, N. A.; Jha, Ratnesh Kumar; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Non-isothermal decomposition of the tetrapropylammonium cations (TPA(+)) intercalated in silicalite-1 framework has been carried out using thermogravimetric (TG) analysis and high temperature powder X-ray diffraction (HTXRD) techniques. Conversion factor for template decomposition is calculated using two methods viz., % weight loss from the thermogravimetric analysis and changes in the intensities of the Bragg reflections 101/011 and 200/020 in the HTXRD patterns scanned at different temperatures (range 298823 K). The calculated apparent activation energy for template decomposition in air was 129 and 125 kJ mol(-1), respectively, for the two techniques TG and HTXRD, calculated using the Kissinger method. By Flynn-Wall-Ozawa approach of isoconversion, apparent activation energy for template decomposition in air was 123 and 124 U mol-1, respectively, for TG and HTXRD data. The reaction order was determined using the method of Kennedy and Clark and it is similar to 2 by both the techniques. The second order of template decomposition can be attributed to the fact that TPA+ is positioned in two different orientations inside the silicalite-1 framework. Template removal occurs with a contraction in unit cell dimensions. There is a decrease in the lattice parameters of the as-synthesized silicalite-1 sample after removal of template from the framework. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: HTXRD; non-isothermal kinetics; Silicalite-1

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15

Thermal stability of mesoporous SBA-15 and Sn-SBA-15 molecular sieves: an in situ HTXRD study - Shah, Pallavi; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Highly ordered SBA-15 and Sn-SBA-15 mesoporous molecular sieves with Si/Sn = 80, 60, 40 and 10 have been prepared through direct synthesis route under milder acidic conditions, which were used for the in situ high temperature X-ray diffraction (HTXRD) studies in the temperature range 298-1573 K for the first time in the literature. SBA-15 is found to be thermally stable up to 1473 K and appearance of alpha-cristobalite was observed at 1573 K also supported by the thermogravimetric (TG) data. A strong negative thermal expansion was observed on heating from 298 to 1573 K (alpha(a) = -4.3 x 10(-6) K-1). Sit containing samples (Si/Sn = 80 and 60) showed a positive thermal expansion (6.75 x 10(-6) K-1 and 9.04 x 10(-6) K-1, respectively). On the other hand, the samples with Si/Sn = 40 and 10 showed a strong negative thermal expansion (-4.12 x 10(-6) K-1 and -7.56 x 10(-6) K-1) similar to SBA-15. The linear thermal expansion coefficient varied in the order: Si/Sn = 60 > 80 > 40 > 0 > 10. Sn4+ ions exhibit both tetrahedral and octahedral coordination depending upon the location of these ions either on the walls of the silica (Si/Sn = 80 and 60) or in the corona region of the structure (Si/Sn = 40 and 10), respectively. The thermal decomposition of the samples (TG data) is correlated to the thermal expansion behavior (HTXRD data). The decomposition behavior of template ions located within the pores is strongly influenced by the presence of Sn in the framework and a `soft' interaction probably exists between the template ions and the Sn sites. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: HTXRD studies; phase transitions; Sn-SBA-15; TG data; Thermal expansion

Enhanced negative thermal expansion in MFI molecular sieves by varying framework composition - Bhange, Deu S.; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2010)
In the present investigations we have carried out the high temperature X-ray diffraction (HTXRD) studies on the metallosilicate molecular sieves iron silicalite-1 (FeS-1) samples of different Si/M ratios (Si/Fe = 50, 75, 100 and infinity) for their negative thermal expansion (NTE) behavior. All the samples exhibit NTE behavior in the temperature range 373-773 K. Systematic increase in negative thermal expansion coefficient is observed as a function of increasing Fe content in the MFI framework. Strength of the negative thermal expansion increases in the order Si/Fe = infinity < 100 < 75 < 50. It is concluded that by changing the composition of the framework of MFI, enhanced negative thermal expansion can be obtained. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HTXRD; Negative thermal expansion; Silicalite-1

Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15